Toxic Effects of Amanitins: Repurposing Toxicities toward New Therapeutics - Le Daré, Brendan (Toxins (Basel), 2021)
The consumption of mushrooms has become increasingly popular, partly due to their nutritional and medicinal properties. This has increased the risk of confusion during picking, and thus of intoxication. In France, about 1300 cases of intoxication are observed each year, with deaths being mostly attributed to Amanita phalloides poisoning. Among amatoxins, α- and β-amanitins are the most widely studied toxins. Hepatotoxicity is the hallmark of these compounds, leading to hepatocellular failure within three days of ingestion. The toxic mechanisms of action mainly include RNA polymerase II inhibition and oxidative stress generation, leading to hepatic cell apoptosis or necrosis depending on the doses ingested. Currently, there is no international consensus concerning Amanita phalloides poisoning management. However, antidotes with antioxidant properties remain the most effective therapeutics to date suggesting the predominant role of oxidative stress in the pathophysiology. The partially elucidated mechanisms of action may reveal a suitable target for the development of an antidote. The aim of this review is to present an overview of the knowledge on amanitins, including the latest advances that could allow the proposal of new innovative and effective therapeutics.